The means of cognitive information conveyance in technical translation. (March 2019) - Milostivaya, A; Makhova, I; Tchudnova, O; Sidelnikova, A; Simonyan, A
Abstract: The purpose of this article is to review various approaches to translation of cognitive information in English technical text into Russian. The focus of this study is to specify the equivalent translation strategies used to convey English technical terms and abbreviations being the source of cognitive information. The analysis of the empirical material, i.e., the original and translation of the English photographic equipment manual, revealed that, possible equivalents, equivalent counterparts and such translational transformations as omission of redundant elements, lexeme addition, generalization, semantic modulation and complete transformation are predominant choices. We have described the following two basic strategies for translating abbreviations. The first one is applied to common, frequently used technical terms and actualizes the reference to the dictionary equivalents; the second strategy is applied to terms specific for the analyzed photo printer manual and results in the use of the source text words.